2017 PRESIDENTIAL ELECTION IN KENYA CONTEXTUALIZED ON THE CONCEPT OF DEMOCRACY - Manyara, Ibrahim J. (Advances in Social Sciences Research Journal, 2020)
ABSTRACT This paper attempts to examine the controversy intertwined in the concept of democracy in theory and practice. It is argued that in political discourses and electoral processes in a State, the concept has been as controversial as it is from individual perspectives. In whichever situation, the proponents are convinced that they are indeed right yet they cannot all be true at the same time. After an election in a State, one set of politicians, voters and election observers will pass a verdict that the process was democratic while at the same time another set of politicians, voters and elections observers will dismiss the elections as flawed and undemocratic. In an attempt to seek answers to this controversy, the paper is divided into three parts. Part A engages in a detailed Ontological and Epistemological analysis of the views and perspectives of theorists and scholars in all historical epochs of academic development. Part B captures the case study of the 2017 presidential elections in Kenya while in Part C author attempts to contextualize the 2017 presidential elections in Kenya on the concept of democracy in an attempt to assess whether the elections were democratic or otherwise based on the researcher’s research findings of the elections. The paper combines both qualitative and quantitative approaches and is anchored on the investment theory of elections and game theory as the theoretical underpinnings. This study concludes that the 2017 presidential elections in Kenya were democratic and undemocratic at the same time. Keywords: Ontology, Epistemology, Game theory, Investment theory of party competition.